Introducing Indonesian Journal of Educational Research and Technology: A Bibliometric Analysis Study - Nandiyanto, Asep Bayu Dani; Al Husaeni, Dwi Fitria; Al Husaeni, Dwi Novia (Journal of Advanced Research Design, 2025)
The research objective was to analyse bibliometric analysis from publications in the Indonesian Journal of Educational Research and Technology (IJERT) from 2021 to 2022. The bibliometric analysis was done using VOSviewer, R Studio and PoPv7 with the Google Scholar database. This study verified the impact of IJERT on internationalization. IJERT has a homogeneous scope in the fields of education. Research in the IJERT journal can become a medium for collaboration locally, regionally and internationally. IJERT does not touch Asian countries only but also other countries in Africa, Europe and Australia. Researchers who plan to publish their works in the areas of education and technology might use IJERT as an academic resource. Additionally, it is anticipated that this research would improve local (Indonesian) and regional (ASEAN) researchers’ motivation and passion to conduct the study, particularly in the areas of technology for improving education.